HOMA-AD, inflammation, and adipose tissue dysfunction as key drivers of immunometabolic risk in people living with HIV and type 2 diabetes - Anaya-Ambriz, Elsa J.; Holguín-Aguirre, Tania E.; Méndez-Ríos, Paula Catalina; Alvarez-Zavala, Monserrat; González-Hernández, Luz A.; Andrade-Villanueva, Jaime F.; Martínez Ayala, Pedro; Cabrera-Silva, Rodolfo I.; Sánchez-Reyes, Karina (Frontiers in Endocrinology, 2025)
BackgroundThe increased life expectancy of people living with HIV (PLWHIV), due to the effectiveness of antiretroviral therapy, has been associated with a higher incidence of metabolic disorders such as dyslipidemia, insulin resistance, and adipose tissue redistribution. It has been demonstrated that the secretion of adipokines, particularly adiponectin, a key hormone in the regulation of inflammation and metabolism, is altered by these changes. This study it is intended to evaluate the HOMA-AD index and its correlations with metabolic, inflammatory, and obesity-related parameters.MethodsEighty participants were divided into five groups (PLWHIV, PLWHIV+preT2D, PLWHIV+T2D, PWT2D, and Controls). Clinical history, anthropometric data, and blood samples were collected to assess biochemical parameters. Adiponectin, hs-CRP, IL-6, IL-18, and IL-8 levels were quantified by ELISA. HOMA2-IR, HOMA2-%B, HOMA2-%S, HOMA-AD, and surrogate IR indices (TyG, TyG-BMI, TyG-WHtR, METS-IR, QUICKI) were calculated. Adiposity indices (VAI, DAI) and inflammatory markers (TG/HDL-C, NEU/HDL-C, MON/HDL, PLT/HDL, NLR, PLR) were also evaluated. Analyses were performed using IBM SPSS, GraphPad Prism, and RStudio.ResultsThe discrimination of T2D in PLWHIV was effectively achieved by the indices HOMA-AD, TyG-WHtR, QUICKI, and METS-IR, with AUC values reaching up to 0.9. Moderate correlations were identified between HOMA-AD and METS-IR (R = 0.58), TyG-WHtR (R = 0.53), QUICKI (R = -0.90), DAI (R = 0.45), and VAI (R = 0.44), as well as inflammatory markers hs-CRP (R = 0.30), IL-6 (R = 0.25), and IL-18 (R = 0.27). A cutoff point of HOMA-AD >1 was associated with a significantly increased risk for T2D in PLWHIV (OR = 15.4; 95% CI: 2.79–79.5), x (OR = 1.97), and non-HIV T2D populations (OR = 9.53). These results highlight the importance of HOMA-AD and inflammatory markers in glycemic risk stratification.ConclusionsOur study demonstrates that the HOMA-AD index improves T2D detection in PLWHIV, likely due to its strong association with insulin resistance, systemic inflammation, and adiposity. It emerges as a promising tool to evaluate metabolic and inflammatory status in this population.